2018
DOI: 10.3390/en11030671
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Heat Transfer to an Arc Absorber Designed for a Waste Heat Recovery System around a Cement Kiln

Abstract: A numerical study on combined free convection, forced convection, and radiation heat transfers from an industrial isothermal rotating cylinder (cement kiln) is carried out in this work. The investigation is done by the study of two-dimensional (2D) incompressible turbulent flow around the kiln under steady-and unsteady-state solutions. The results of this study show that the average Reynolds and Rayleigh numbers around the cylindrical kiln are 647,812.1 and 1.75986 × 10 11 , respectively. A heat absorber is sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Previously, the authors showed that the rotating effect mixed by free convection from the kiln is significant and cannot be neglected [17]. This statement is confirmed in Fig.…”
Section: Heat Loss From the Kiln Without Absorbersupporting
confidence: 63%
See 2 more Smart Citations
“…Previously, the authors showed that the rotating effect mixed by free convection from the kiln is significant and cannot be neglected [17]. This statement is confirmed in Fig.…”
Section: Heat Loss From the Kiln Without Absorbersupporting
confidence: 63%
“…By finding the temperature distribution along the kiln length, heat transfer mechanisms including free convection, forced convection, radiation and convection due to rotation of the kiln can be calculated, as represented in Fig. 2(b), by using empirical and analytical correlations as expressed in [16,17].…”
Section: Heat Loss From the Kiln Without Absorbermentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption coefficient and the scattering coefficient could be neglected in the model, and the model was suitable for the analysis because there was no permeable medium in the analytical domain of this study [19]. For a somewhat larger scale with geometry similar to that of this study, Mirhosseini et al [20] conducted 2D numerical analysis on the radiative heat exchange of an arc absorber around a cylindrical cement kiln using an S2S model. Table 5 shows the boundary conditions used for heat flow analysis.…”
Section: Numerical Analysis Model and Boundary Conditionsmentioning
confidence: 99%
“…TEGs are being developed for use in automobiles for generating electricity from exhaust gases in order to improve overall engine efficiency [30]. Several studies have testified TEGs as a viable option for waste heat recovery in domestic, industrial, and other processes [2,[31][32][33]. Recently, TEGs have been introduced in the consumer market as a power device to charge small electronics such as sensors and cell phones by utilizing heat from candles [34] and propane stoves [35].…”
mentioning
confidence: 99%